2006
DOI: 10.1002/jso.20696
|View full text |Cite
|
Sign up to set email alerts
|

Selective use of radioactive iodine in the postoperative management of patients with papillary and follicular thyroid carcinoma

Abstract: Radioiodine remnant ablation (RRA) was developed in the 1960s to "complete a thyroidectomy" in the initial management of papillary and follicular thyroid cancer. By the 1990s, it was claimed that RRA diminished recurrence rates in follicular cell-derived cancer (FCDC) patients and decreased the cause-specific mortality (CSM) in patients more than 40 years old at initial surgery. The international trend for the past decade has been towards routine RRA in most FCDC patients. Clinical guidelines have been produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 50 publications
0
56
0
3
Order By: Relevance
“…Since 1997, many studies have reported the outcomes of PTC and FTC patients who were subjected to radioactive iodine ablation after bilateral lobe resection. It was recognized later on that most of these patients are truly at ''low risk'' of developing life-threatening recurrences (32). This may explain our finding that the inappropriate selection criteria during the late 1990s could have failed to identify the true high-risk FV-PTC or FTC patients, which largely masked the significant effectiveness of total thyroidectomy and radioactive iodine ablation.…”
Section: Discussionmentioning
confidence: 92%
“…Since 1997, many studies have reported the outcomes of PTC and FTC patients who were subjected to radioactive iodine ablation after bilateral lobe resection. It was recognized later on that most of these patients are truly at ''low risk'' of developing life-threatening recurrences (32). This may explain our finding that the inappropriate selection criteria during the late 1990s could have failed to identify the true high-risk FV-PTC or FTC patients, which largely masked the significant effectiveness of total thyroidectomy and radioactive iodine ablation.…”
Section: Discussionmentioning
confidence: 92%
“…In patients with a normal thyroglobulin level, conducting imaging, and laboratory tests and taking a careful history can help to make the differential diagnosis. CT, magnetic resonance imaging (MRI), and US are widely used imaging modalities (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…Both postoperative radioiodine ablation and whole body scanning (WBS) are widely accepted therapeutic regimens for treating differentiated thyroid carcinoma (1)(2)(3). The presence of uptake sites following diagnostic or therapeutic I-131 administration may suggest the need for further therapy with I-131.…”
Section: Introductionmentioning
confidence: 99%
“…There is a major focus on shifting away from routine use of radioactive iodine in low risk thyroid cancer patients, as the survival in this group exceeds 98 %. 5 Unfortunately, patients often ask for scans and ablation to make sure their tumor has not spread to other parts of the body and often insist on overtreatment. Clearly, such overtreatment has no sound biological basis and may have unpleasant sequelae.…”
Section: Schuesslermentioning
confidence: 99%